Application of artificial intelligence to personalize user content in the company’s marketing offers - V. V. Shendrik (Путеводитель предпринимателя)
The growing interest of business in the use of artificial intelligence is determined by the enormous optimization, analytical, predictive and generative capabilities. A pressing issue in these conditions is determining the features of the use of artificial intelligence in specific tasks, operations and business processes of the company. The article reveals aspects of the use of artificial intelligence to personalize user content in the company’s marketing offers. An analysis of modern research on personalization and the use of artificial intelligence tools in marketing is carried out. A list of areas, tools and operations necessary to personalize a company’s marketing based on artificial intelligence is identified. Based on the results of the study, a list of tasks in the company’s marketing is provided that can be solved by modern artificial intelligence tools.